Evaluasi keragaman dan kemajuan seleksi kacang panjang (Vigna unguiculata (L.)) generasi F6 berdasarkan karakter agronomi - Nurul Shintawati; Syaiful Anwar; Florentina Kusmiyati (Jurnal Ilmiah Pertanian, 2022)
Red or purple yardlong bean is one type of yardlong bean that is starting to be developed but has a bitter taste due to its antioxidant content. Improvements in the quality of red or purple yardlong beans can be achieved through crossbreeding. The effective selection of crossbreeding can be seen from the diversity and selection progress. The research purpose was to assess genetic diversity and estimate the value of the selection progress of yardlong beans (Vigna unguiculata (L.)) F6 generation from a crossing between Fagiola IPB and Aura Hijau. The research was conducted at the Agrotechnopark, Diponegoro University, Semarang. The study was arranged in a completely randomized design (CRD) with an unequal number of replications. The results showed that all characters except the number of seeds per plant had low genetic diversity. The high heritability and value of genetic advances were found in antioxidant content. All characters had selection progress except for fresh harvest age and weight of 100 seeds. Partial correlation analysis showed a positive correlation between the character number of dry pods per plant with the number of leaves, the number of seeds per plant, seed weight per plant, and antioxidant content, also the character number of seeds per plant with several leaves and seed weight per plant. A negative correlation showed between the character number of leaves with seed weight per plant and antioxidant content and the character number of seeds per plant with antioxidant content.